Isolation and Screening of Phosphate and Potassium Solubilizing Endophytic Bacteria in Maize (Zea mays L.) - Azizah, Hilya; Rahajeng, Saptini M.; Jatmiko, Yoga D. (Graduate School, Universitas Brawijaya, 2020)
Maize (Zea mays L.) is a functional food source in Indonesia after rice and wheat. Increasing maize productivity can be done by developing a proper environment and nutritional availability during cultivation. The use of endophytic bacteria as biofertilizers is one prospective approach in reducing the synthetic fertilizers in the soil, and improving the absorption of macronutrients, such as nitrogen, phosphate, and potassium, as well. This study aimed to obtain phosphate solubilizing bacteria (PSB) and potassium solubilizing bacteria (KSB). The samples of maize leaves, stems, and roots were isolated using a serial dilution method and selected on a Pikovskaya and Aleksandrov medium. A total of 10 PSB isolates were obtained from PKV selective agar media. The highest density was obtained in the root (8.3x105 CFU.mL-1), stems (5.7x105 CFU.mL-1), and leaves (4.6x105 CFU.mL-1), respectively. Meanwhile, the diversity index of the PSB ranges from 0.7 to 0.78, indicates that the diversity index is high. Four isolates from PSB (AP1.3, AP3.1, AP1.2, and AP1.4) were selected as KSB because of the clear zone formed in Aleksandrov's medium. The highest production of phosphate and potassium was obtained by AP1.3 with value 12.11 µg.mL-1 and 8.38 µg.mL-1 at 72h and 15d, respectively. Therefore, these isolates potential to be used as an organic fertilizer (biofertilizers). Keywords: Biofertilizer, endophytic bacteria, phosphate, potassium.